Second Primary Melanoma: Risk Factors, Histopathologic Features, Survival, and Implications for Follow-Up. Issue 10 (October 2016) - Jones, Maris S.; Torisu-Itakura, Hitoe; Flaherty, Devin C.; Schoellhammer, Hans F.; Lee, Jihey; Sim, Myung-Shim; Faries, Mark B.
The impact on survival of a second primary melanoma (SPM) is unclear. We used our melanoma center's database to examine clinicopathologic risk factors and outcomes of stage 0 to IV cutaneous melanoma in patients with one versus two primaries. Among 12, 325 patients with primary melanoma, 969 (7.86%) developed SPM. SPMs were significantly thinner than autologous primary melanomas ( P = 0.01), and 451 SPM patients had better overall and melanoma-specific survival than 451 prognostically matched non-SPM patients ( P < 0.0001 and 0.0001, respectively) at a median follow-up of 142.37 months. Patients with cutaneous melanoma are at high risk for development of SPM, but the development of SPM does not seem to impair survival.